2019
DOI: 10.1111/prd.12263
|View full text |Cite
|
Sign up to set email alerts
|

Oral autoimmune vesicobullous diseases: Classification, clinical presentations, molecular mechanisms, diagnostic algorithms, and management

Abstract: Vesicobullous diseases are a large group of disorders with different etiologies, pathogenesis, and prognoses that affect the skin, the mucosal surfaces, or both. The clinical sign that marks all vesicobullous diseases is the onset of vesicles or bullae, defined as skin/mucosal lesions with a subcorneal or suprabasal intraepithelial detachment within the epithelium (acantholysis) or with a subepithelial detachment between the epithelium and the lamina propria. Clinical and histologic findings vary markedly amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 83 publications
0
49
0
4
Order By: Relevance
“…19 blisters can present on any part of the oral mucosa but frequently develop in areas subjected to frictional forces. 20 Due to the fragile nature of the blisters, areas of shallow, widespread painful erosions that can persist for months are frequently noted on examination ( Figure 8). Due to the serious and potentially fatal nature of pV, it is imperative that it is diagnosed early and treated with appropriate immunosuppression therapy.…”
Section: Pemphigus Vulgarismentioning
confidence: 99%
“…19 blisters can present on any part of the oral mucosa but frequently develop in areas subjected to frictional forces. 20 Due to the fragile nature of the blisters, areas of shallow, widespread painful erosions that can persist for months are frequently noted on examination ( Figure 8). Due to the serious and potentially fatal nature of pV, it is imperative that it is diagnosed early and treated with appropriate immunosuppression therapy.…”
Section: Pemphigus Vulgarismentioning
confidence: 99%
“…24 However, a definitive diagnosis may be possible only with microscopic examination. 2,[4][5][6] Once a definitive diagnosis of the cause of DG has been established, special multidisciplinary coordinated approaches should be taken because; MMP can affect conjunctiva which may result in subconjunctival scarring (symblepharon) and eventually permanent blindness 22,25 , PV is a serious mucocutaneous disease which can be fatal if untreated, 20,26 and OLP has a risk for malignant transformation. 18 The main limitation of this study was the limited sample size and relatively short observation period.…”
Section: Discussionmentioning
confidence: 99%
“…3 A careful medical history and intraoral examination for erythematous gingiva and other oral lesions with specific appearances are extremely important in establishing a clinical diagnosis. 2,4 However, DG-related mucocutaneous diseases frequently share similar clinical manifestations, so, further diagnostic methods, based on biopsy for histopathologic and direct immunofluorescence analysis (DIF), are considered to be the gold standard in diagnosis. 1,5,6 Previous studies demonstrated that patients with oral mucosal diseases are widely misdiagnosed, leading to multiple consultations and insufficient treatments.…”
Section: Intruductionmentioning
confidence: 99%
“…This large group of diseases can affect the oral mucosa alone or in combination with skin lesions. Leuci et al discuss the most frequent autoimmune vesiculo‐bullous disorders: pemphigus vulgaris, mucous membrane pemphigoid, bullous pemphigoid and linear IgA disease. They provide a comprehensive account of classification, etiology, molecular pathogenesis, clinical features, diagnosis and management.…”
Section: Autoimmune Vesiculo‐bullous Diseasesmentioning
confidence: 99%